Uncommon Presentation of Stromal Tumor Causing Small Bowel Obstruction: A Case Report - Zamin Adigozalli; Rasim Khalilov; Steffen Seyfried (Caucasian Medical Journal)
This case report describes a rare presentation of gastrointestinal stromal tumor (GIST) causing mechanical small bowel obstruction in a 30-year-old female patient with a history of hepatitis B. Initial misdiagnosis as gastritis led to delayed recognition of the underlying pathology. Emergency laparoscopic intervention revealed mixed epithelioid and spindle cell GIST with high risk features, prompting segmental small bowel resection. Histopathological examination confirmed a PDGFRA mutation, loss of c-kit and DOG 1 expression, and a high mitotic rate, categorizing the tumor as high risk. This case highlights the importance of considering GIST in the differential diagnosis of abdominal symptoms and emphasizes the need for timely intervention to prevent complications.